Cellulose fiber-reinforced high-density polyethylene composites—Mechanical and thermal properties - Mulinari, Daniella R; Voorwald, Herman JC [UNESP]; Cioffi, Maria OH [UNESP]; da Silva, Maria LCP (SAGE Publications, 2017)
In this investigation, the thermal and mechanical properties of cellulose fibers from sugarcane bagasse reinforced with high density polyethylene composites were evaluated. Cellulose fibers were modified with hydrous Zr oxide to clean the fiber surface and improve the fibers–matrix adhesion. Composites were manufactured using a thermokinetic mixer process and the fiber content was responsible for 5, 10, 20, 30, and 40wt% in the composition. The chemical modification of the cellulose fibers with zirconium oxide was verified by FTIR analysis and the fibers’ morphological aspects by SEM. After the chemical modification, the FTIR results showed reduction of OH bonds. SEM characterization showed that the modification changed the morphology of fibers. The results show that composites reinforced with modified cellulose fibers have an improvement in the thermal and mechanical properties, when compared to the non-cellulose fibers. In addition, an enhancement on the mechanical properties of composites was found, i.e. a gain of 122.4% compared to neat polymer at 40wt.% fiber loading in Young’s modulus. The thermal properties show a slight decrease with increase of modified cellulose.
Keywords: cellulose; composite; mechanical properties; Sugarcane bagasse; thermal properties; ZrO2.nH2O